Land Acquisition Mechanism for Public Interest on Traditional Land: A Study of Rempang Eco City - Paramyta, Dwi Sartika; Nadapdap, Gindo; Srikusuma, M. Rohmidhi; Simbolon, Juliana Permata Sari (Jurnal Penelitian Medan Agama, 2024)
Indonesia, as an agrarian nation, faces the complexities of land management, particularly concerning customary land. The Basic Agrarian Law (UUPA) of 1960 and Law No. 2 of 2012 regulate land acquisition for public purposes. However, their implementation often triggers conflicts among the government, private entities, and indigenous communities. The case of the Rempang Eco City serves as a vivid illustration of such conflicts, highlighting the need to balance development interests with the protection of indigenous community rights. This study employs a normative juridical method with legal and conceptual approaches. Primary, secondary, and tertiary legal materials are analyzed through literature review and documentation. An inductive approach and legal interpretation are applied to understand customary land acquisition in the context of public interest. Customary land rights (hak ulayat) are recognized under the 1945 Constitution and the Basic Agrarian Law (UUPA) of 1960, provided they do not conflict with national interests. The Rempang Eco City case reveals tensions between the recognition of indigenous rights and the demands of national development. An ideal solution must prioritize deliberation, the acknowledgment of indigenous rights, and fair compensation for indigenous communities, adhering to the principles of social justice and sustainable development.The Rempang Eco City project underscores the importance of recognizing indigenous rights in land acquisition processes. Indigenous community participation, transparent consultations, and fair compensation are crucial steps to prevent conflicts. Therefore, a justice-based approach that emphasizes social welfare and human rights protection must take precedence in the process of acquiring customary land for public purposes.